2020
DOI: 10.3389/fmars.2020.590565
|View full text |Cite
|
Sign up to set email alerts
|

Wave-Induced Distribution of Microplastic in the Surf Zone

Abstract: In this study, the wave-induced distribution of 13 microplastic (MP) samples of different size, shape, and density was investigated in a wave flume with a sandy mobile beach bed profile. The particle parameter were chosen based on an occurrence probability investigated from the field. MP abundances were analyzed in cross-shore and vertical direction of the test area after over 40,000 regular waves. It was found, that MP particles accumulated in more shallow waters with increasing size and density. Particles wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 63 publications
(103 reference statements)
0
25
0
Order By: Relevance
“…39 This condition is similar to the results found at this research location, where the concentration of heavy metals tends to increase in the northern monsoon due to the effect of current and wave dynamics, which are the driving force for marine dynamics that carry and spread pollutants in waters. 40 Koropitan and Cordova (2017) stated that flow is a component of heavy metal transport from a river transported into open water, thereby increasing its value in the aquatic ecosystem. 41 Budiyanto and Lestari (2017) examined the difference between metals in the eastern (March) and the southern seasons (June).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 This condition is similar to the results found at this research location, where the concentration of heavy metals tends to increase in the northern monsoon due to the effect of current and wave dynamics, which are the driving force for marine dynamics that carry and spread pollutants in waters. 40 Koropitan and Cordova (2017) stated that flow is a component of heavy metal transport from a river transported into open water, thereby increasing its value in the aquatic ecosystem. 41 Budiyanto and Lestari (2017) examined the difference between metals in the eastern (March) and the southern seasons (June).…”
Section: Resultsmentioning
confidence: 99%
“… 39 This condition is similar to the results found at this research location, where the concentration of heavy metals tends to increase in the northern monsoon due to the effect of current and wave dynamics, which are the driving force for marine dynamics that carry and spread pollutants in waters. 40 …”
Section: Resultsmentioning
confidence: 99%
“…39 This condition is similar to the results found at this research location, where the concentration of heavy metals tends to increase in the northern monsoon due to the effect of current and wave dynamics, which are the driving force for marine dynamics that carry and spread pollutants in waters. 40 Koropitan and Cordova (2017) stated that flow is a component of heavy metal transport from a river transported into open water, thereby increasing its value in the aquatic ecosystem. 41 Budiyanto and Lestari (2017) examined the difference between metals in the eastern (March) and the southern seasons (June).…”
Section: Resultsmentioning
confidence: 99%
“…There exist some recent experimental studies of microplastics transport in laboratories [11][12][13][14]. Forsberg et al (2020) [11] performed physical simulation experiments with fresh water (no salinity) in a CASH (Canal Aero-Sedimento-Hydrodynamics) wind-wave flume, which had a length of 6 m and a width of 0.5 m and was equipped with a linearly sloping bathymetry.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that plastic properties, shape, and density, govern the behavior of plastic litter in the nearshore zone [11]. Kerpen et al (2020) also studied the distribution of microplastics (13 microplastic samples of different sizes and densities) having different nominal diameters (from 0.5 to 4.1 mm) and a round shape with a wave-induced flow in a laboratory two-dimensional flume that had a length of 6.7 m, a width of 0.3 m, and a depth of 0.45 m. The flume is equipped with a flap-type wavemaker for monochromatic wave generation with a water depth of 0.3 m. They also suggested that size and density affect the distribution of microplastics [12].…”
Section: Introductionmentioning
confidence: 99%